Effect of Dietary Supplementation of Azolla Meal on Feed Intake and Digestibility in Sangamneri Kids - P. P. Bhadake; M. G. Mote; U. S. Gaikwad; M. U. Tanpure (Indian Journal of Animal Nutrition, 2024)
Twenty-four Sangamneri kids aged between 3 to 6 months and weighing between 8 to 12 kg were selected for the experiment and distributed into four treatments viz., T0 (control), T1 (10 % concentrate replaced by Azolla meal), T2 (15% concentrate replaced by Azolla meal) and T3 (20 % concentrate replaced by Azolla meal). The feeding trial was conducted for the period of 3 months. Roughages to concentrate ratio was kept as 67:33. Feed samples and faeces of different treatments were collected and chemically analyzed. The DM, CP, CF, EE, NFE, total ash, lignin and silica content in Azolla meal were 92.12, 22.41, 16.30, 2.87, 53.15, 7.90, 9.35 and 3.12 percent respectively and the concentrate mixture had 90.23, 19.13, 8.2, 4.95, 62.82, 4.6, 1.72 and 1.31 percent DM, CP, CF, EE, NFE, total ash, lignin and silica respectively. Average daily dry matter intake was 0.405, 0.520, 0.590 and 0.509 (kg/day) in T0, T1, T2 and T3 respectively. Average DM intake per 100 kg body weight during period of experiment were 2.86, 3.57, 3.81 and 3.50 per cent. Feed consumption difference due to different treatments were found statistically significant (P